2013
DOI: 10.1007/s10067-013-2174-x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of vitamin D levels on the assessment of disease activity in rheumatoid arthritis

Abstract: Disease activity in rheumatoid arthritis (RA) is assessed by a combination of objective and subjective tests, combined to produce a disease activity score in 28 joints (DAS28). There is some evidence that RA disease activity, as assessed by DAS28, can be influenced by vitamin D levels. It is difficult to know whether this is due to a true immunomodulatory effect of vitamin D or a more subjective effect of low vitamin D on pain perception. We addressed this issue by comparing vitamin D levels with disease activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
36
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(39 citation statements)
references
References 12 publications
2
36
1
Order By: Relevance
“…However, we found no statistical negative correlation between vitamin D levels and DAS28. In some previous studies, no significant association was determined between disease activity and vitamin D levels and their results were consistent with our study [10,14,15]. On contrary, some studies reported a significant negative correlation [9,[11][12][13].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…However, we found no statistical negative correlation between vitamin D levels and DAS28. In some previous studies, no significant association was determined between disease activity and vitamin D levels and their results were consistent with our study [10,14,15]. On contrary, some studies reported a significant negative correlation [9,[11][12][13].…”
Section: Discussionsupporting
confidence: 91%
“…However, the complaints due to vitamin D deficiency may lead to the delusion which increases the disease activity in cases with RA. It is reported that the clinician should consider this situation when assessing the activation of the disease [10].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This might have major implications for subsequent management, as they may then be subjected to treatment escalation in spite of the absence of any ongoing disease activity. This carries implications at both clinical and financial levels [46]. Hence, clinicians need to be aware disease activity in their study participants.…”
Section: Discussionmentioning
confidence: 99%
“…Through Editorial recruited from 22 Italian rheumatology centers, concluded that lower serum 25(OH)D 3 levels were associated with active disease by a DAS 28 score of >3.1, lack of remission and poor response to therapy, even after adjusting for sunlight exposure and BMI [11]. In a recent study from the UK, however, there was no significant correlation between 25(OH)D 3 and DAS 28 scores with or without the inclusion of VAS, while there was a significant relationship between 25(OH)D 3 and VAS itself [12]. The mean DAS 28 scores were greater in 25(OH) D 3 -deficient patients, being explained by their higher VAS scores.…”
mentioning
confidence: 90%